Інтенсифікація технології одержання біогазу та комплексних добрив з осадів міських стічних вод - Іванченко, А. В.; Бєлянська, О. Р. (НТУ "ХПІ", 2015)
Зроблено аналіз перспектив впровадження технологій отримання біогазу і комплексних добрив з осадів міських стічних вод в Україні та за кордоном. Вперше встановлено вплив попереднього диспергування осадів стічних вод на тривалість процесу анаеробного зброджування. Показано, що диспергування прискорює швидкість виділення біогазу в 2,2 рази. Проведено хімічний аналіз збродженого комплексного добрива на основі відходів міських очисних споруд. Розроблено технологічну схему вузлу одержання біогазу та комплексного добрива з використанням диспергатора і установки анаеробного зброджування.

The analysis prospects introduction technologies for production biogas and fertilizer from municipal sewage sludge in Ukraine and abroad. It is noted, that one of the unresolved issues in the implementation of biogas plants in Ukraine remains the reduction of duration their work. For the first time effect of preliminary dispersion sewage sludge the duration of the process anaerobic digestion. In a laboratory reactor was loaded with 8 g of sludge at the exit from the installation mass of digested sludge was 5,44 g (68 %), 2,56 g (38 %) raw materials refracted into biogas volume 0,07 dm³. It is shown that the dispersion accelerates speed separation of biogas in 2,2 times. Investigated the structure dispersed activated sludge, as a result of dispersing it becomes thicker and processes have been intensified. Chemical analysis fermented complex fertilizers based on the urban waste water treatment facilities this composition, %: organic – 62,8; total nitrogen (N) – 6,5; phosphorus (P₂O₅) – 4,2; potassium (K₂O) – 0,4. The technological scheme the site biogas production and complex fertilizers with the use of a dispersant and anaerobic digestion plant.
Intensification technology for production biogas and fertilizer from municipal sewage sludge
Keywords: мул активний; диспергування; зброджування анаеробне; activated sludge; dispersing; anaerobic digestion